2019
DOI: 10.1038/s41598-019-48762-5
|View full text |Cite
|
Sign up to set email alerts
|

MitCHAP-60 and Hereditary Spastic Paraplegia SPG-13 Arise from an Inactive hsp60 Chaperonin that Fails to Fold the ATP Synthase β-Subunit

Abstract: The human mitochondrial heat shock protein 60 (hsp60) is a tetradecameric chaperonin that folds proteins in the mitochondrial matrix. An hsp60 D3G mutation leads to MitCHAP-60, an early onset neurodegenerative disease while hsp60 V72I has been linked to SPG13, a form of hereditary spastic paraplegia. Previous studies have suggested that these mutations impair the protein folding activity of hsp60 complexes but the detailed mechanism by which these mutations lead the neuromuscular diseases remains unknown. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Structural studies on both mutants have highlighted the strong effect nucleotide binding has on the mutant mtHsp60 proteins. Electron microscopy and dynamic light scattering studies showed that mtHsp60 harboring either the D29G or V98I mutation dissociated into monomers upon the addition of nucleotide (ATP and ADP had the same effect on complex disruption) (Wang et al, 2019). The nucleotide free (APO) state was able to oligomerize and was stable under experimental conditions suggesting that the mutations have deleterious structural effects mainly during nucleotide binding and or hydrolysis.…”
Section: Chaperonopathies and The Role Of Mthsp60 In Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Structural studies on both mutants have highlighted the strong effect nucleotide binding has on the mutant mtHsp60 proteins. Electron microscopy and dynamic light scattering studies showed that mtHsp60 harboring either the D29G or V98I mutation dissociated into monomers upon the addition of nucleotide (ATP and ADP had the same effect on complex disruption) (Wang et al, 2019). The nucleotide free (APO) state was able to oligomerize and was stable under experimental conditions suggesting that the mutations have deleterious structural effects mainly during nucleotide binding and or hydrolysis.…”
Section: Chaperonopathies and The Role Of Mthsp60 In Diseasementioning
confidence: 99%
“…MtHsp60 can alternate between single and double heptameric ring conformations upon nucleotide binding and following hydrolysis ( Viitanen et al, 1992 , 1998 ; Nielsen and Cowan, 1998 ; Nielsen et al, 1999 ; Levy-Rimler et al, 2001 ; Nisemblat et al, 2014 , 2015 ; Vilasi et al, 2014 , 2018 ; Enriquez et al, 2017 ; Jebara et al, 2017 ; Bhatt et al, 2018 ; Wang et al, 2019 ; Gomez-Llorente et al, 2020 ). Furthermore, the structure of the ATP bound conformation has recently been solved, both by crystallography and electron microscopy.…”
Section: The Chaperonin Protein Folding Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…b Because of the use of T4 as the transducing phage, the expected linkage between the Tet R and Cam R genes is higher than that reported by Hansen et al (2002). the HSP60 chaperone complex (Wang et al 2019). These disease-associated amino acids are located in close proximity to each other and the ATP-binding domain, yet are not directly in contact with the bound ATP (Fig.…”
Section: Discussionmentioning
confidence: 98%